PROBLEM BASED LEARNING MODEL ANALYSIS IN 21ST CENTURY ISLAMIC RELIGIOUS EDUCATION LEARNING - Alfiatus Sholiha; Zakiyatul Nisa; Irma Soraya; Asep Saeful Hamdani (Fakultas Tarbiyah, Universitas Ibrahimy, 2024)
This study aims to gather information and explore the application of the problem based learning model in 21st century PAI learning as an effort to develop students' critical culture. This study uses the library research method with a descriptive analysis approach through examining library sources in the form of books, journals, scientific papers, literature relevant to the research theme.The results of this study are that the problem based learning model is one of the relevant models used in PAI learning to provide meaningful learning and in-depth understanding to students. Because the problem based learning model is learning by exposing students to problems in the real world so that students will get used to thinking critically and become independent learners.